Serum endocan levels in women with restless legs syndrome - Celik K (Dove Medical Press, 2015)
Kenan Celik,1 Mehmet A Cikrikcioglu,1 Gulistan Halac,2 Elif Kilic,3 Siddika Ayhan,3 Nihal Ozaras,4 Kemal Yildiz,5 Rabia S Yildiz,1 Mehmet Zorlu,1 Cumali Karatoprak,1 Mustafa Cakirca,1 Muharrem Kiskac1 1Department of Internal Medicine, 2Department of Neurology, 3Department of Biochemistry, 4Department of Physical Medicine and Rehabilitation, Medical Faculty, Bezmialem Vakif University, Fatih, 5Department of Internal Medicine, Private Medicana International Istanbul Hospital, Beylikdüzü, Istanbul, Turkey Background: Endocan is a recently introduced marker of endothelial dysfunction. The objective of this study was to compare serum endocan levels in patients with restless legs syndrome (RLS) and control subjects in order to elucidate whether RLS is associated with endothelial dysfunction. Methods: A total of 31 drug naïve female patients with RLS and 31 age- and BMI-matched women were included in the study. Patients with pathological or physiological conditions or with a history of medication use that could potentially influence endothelial functions were excluded, as well as those with alcohol or drug abuse history. The two groups were compared with routine blood tests and serum endocan levels. Results: Patients with RLS had lower serum endocan levels than the controls (P=0.037). There was a negative bivariate correlation between RLS severity score and serum endocan levels (r=-0.406, P=0.023). While white blood cell count was significantly higher in RLS group, 25-hydroxy vitamin D3, vitamin B12, transferrin saturation rate, and HDL-cholesterol were significantly lower. Creatininemia and diastolic blood pressure were also marginally insignificantly lower in RLS group. Due to the presence of differences between two groups in these variables, a linear regression analysis was performed that showed a positive association between endocan and creatininemia (β=0.310, P=0.022), and a negative association between endocan and RLS (β=-0.502, P<0.001). Conclusion: The results of this study seem to suggest that patients with RLS may have better endothelial functions when compared with the general population and that these patients may be better protected against atherosclerosis. Keywords: endocan, restless legs syndrome, RLS, atherosclerosis, endothelial